Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20181397
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge and behavior of medical personnel regarding skin cancer, sun-related hazards and sunscreen utilization at King Abdulaziz University Hospital, Jeddah

Abstract: Original Research ArticleAwareness, knowledge and behavior of medical personnel regarding skin cancer, sun-related hazards and sunscreen utilization at ABSTRACT Background: Worldwide, skin cancer is a major public health concern. It is a common malignancy in Saudi Arabia. The three most prevalent types of skin cancer are basal cell carcinoma, squamous cell carcinoma and melanoma. Exposure to ultraviolet (UV) radiation is the most common modifiable risk factor to lower the risk of the leading types of skin canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
3
5
1
Order By: Relevance
“…Out of the 93 participants, 60 (64.5%) were knowledgeable about sun radiation diseases, 17 (18%) about skin cancer, 6 (6%) about pigmentation, and 4 (4%) about sunburns, while 2 (2%) knew about freckles, spot-darkening, and wrinkles. These results are consistent with those of another study, which found that participants had adequate knowledge of skin cancer risk factors and sun protection measures [10]. Another survey reported that sunburns and skin cancer prevention, as well as the preservation of light skin color and the avoidance of dark patches, were among the top reasons for using sunscreen [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Out of the 93 participants, 60 (64.5%) were knowledgeable about sun radiation diseases, 17 (18%) about skin cancer, 6 (6%) about pigmentation, and 4 (4%) about sunburns, while 2 (2%) knew about freckles, spot-darkening, and wrinkles. These results are consistent with those of another study, which found that participants had adequate knowledge of skin cancer risk factors and sun protection measures [10]. Another survey reported that sunburns and skin cancer prevention, as well as the preservation of light skin color and the avoidance of dark patches, were among the top reasons for using sunscreen [11].…”
Section: Discussionsupporting
confidence: 89%
“…Lack of efficacy and cost are the most common reasons for not using sunscreen [11]. Another interesting finding was that people do not use sunscreen because they are lazy, tired, or don't have time, and 27% believe they do not need it [10].…”
Section: Discussionmentioning
confidence: 99%
“…4,21,26 Nevertheless, a higher level of knowledge is not always directly related to better photoprotective behaviors, as noted in previous studies. 3,14 Further analysis in this study revealed that knowledge and behavior were significantly associated (P = 0.02).…”
Section: Discussionmentioning
confidence: 62%
“…These values are higher than those reported by a study on sunscreen use among medical personnel in Saudi Arabia, in which only 12.3% of the participants were found to always use sunscreen during their daily activity. 14 Relative to other studies, students from medicine-related disciplines have been observed to typically exhibit greater knowledge regarding but little to no difference in the habit of using sunscreen, 7 which indicates that factors other than education, such as female sex, might have a greater influence on photoprotective behaviors. 4,7 This study referred to the guidelines on sunscreen use of the American Academy of Dermatology, including those regarding the ideal times of sunscreen application; amount of sunscreen to be applied; level of protection (sun protection factor, SPF) needed; frequency, methods, and sites of application; and reapplication of sunscreen.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation